Literasi Stunting pada Masa Pandemi Covid-19 untuk Ibu Balita dan Kader Posyandu Desa Umbulrejo Kapanewon Ponjong Kabupaten Gunung Kidul - Siswati, Tri; Widyawati, Herni Endah; Khoirunissa, Salma; Kasjono, Heru Subaris (Universitas Nusantara PGRI Kediri, 2021)
Empowering women was the most important efforts to create the nation's next-generation, including efforts to alleviate stunting children. The limitation of health knowledge was one of indirect determinant stunting children. Literacy may increase woman knowledge about children care, so they can meet nutritional needs and environmental health. This was a community engagement with classical methods, interactive discussions, brainstorming through virtual meetings with google-meet and WhatsApp groups about stunting on 18-21 September 2020. Participants were mothers and cadres at highest prevalance stunting children in Yogyakarta (Umbulrejo Village, District Ponjong, Gunung Kidul Regency) as many as 50 women. The output of literation was measured by attendance (75%), increasing of knowledge 25%, and participant anthusiasm. Overall, this was meet the target, as many as 80% attendance of participants, 32% increase of knowledge, and enthusiastically participating. Virtual literacy and telecounseling were effective method to provide education and health counseling in Covid-19 pandemic context.